Aplikasi Inventory Peralatan Mekanik Unit BRT UNAS Berbasis Web Menggunakan Metode Black-Box dan White-Box Testing - Supriyanto Supriyanto; Iskandar Fitri; Nurhayati Nurhayati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The BRT Unit (Household Section) in carrying out its duties requires several work tools that are used to support the work process properly and correctly. The tools used are tools that are stored in the BRT Unit room and when they want to be borrowed, the employee only takes these tools which have been previously ordered by the head of the BRT unit and then recorded by the room operator. In the process, the data on equipment borrowing is not guaranteed to be stored because it is only recorded on a book or paper provided by the BRT unit. Furthermore, in the return process, borrowed tools sometimes have some tools that are no longer suitable for use, to find out how many inventory tools are borrowed and find out the stock of tools available so as to facilitate job data collection. The test method for the application uses white-box testing with the value of Cyclomotic Complexity = 9, Region = 9 and Independent Path = 9 so that the mechanical Inventory application is produced.